Insulin Prescription Pattern among Type 2 DM patients visiting Outpatient Department at a Tertiary Hospital in Kathmandu, Nepal - Shrestha, Hari Kumar; Tamrakar, R.; Shrestha, Ashish; Amatya, S.R. (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Background: Management of Type 2 Diabetes Mellitus includes nonpharmacological and pharmacological interventions of which insulin remains one of the most effective methods for achieving glycemic control, either alone or in combination with oral anti-diabetic medications. Effective usage of insulin in the management of glycaemia remains a challenge in developing countries like Nepal. To best of our knowledge, there is not any study regarding insulin prescription pattern on Type 2 Diabetes Mellitus patients using insulin from Nepal, so we studied the prescription pattern of insulin on insulin using Type 2 Diabetes Mellitus patients. Methods: Patients aged 30 years or above who present in Dhulikhel Hospital outpatient clinic during the period from January 2015 to June 2015 with diagnosis of Type 2 Diabetes Mellitus diagnosed at least for 6 months and were taking injection insulin at least since last 3 months were enrolled in this cross sectional, observational study. Results: Forty-five study participants had a mean age of 56.6 ±10.95 year, body mass index of 23.97 4.72 kg/m2, Diabetic duration of 10.33 6.41 years and HbA1c of 8.53 ±1.53%. Fifty-three percent were female and almost all study participants (96%) were taking Oral Antidiabetic Drugs along with Insulin. Sixty-three percent of participants were using Premix insulin whereas 33% were using basal insulin alone. Mean Insulin dose was 28.96 11.75 units per day. Among them, 80% were “self” injecting insulin and 53% were using Glucometer. Conclusion: Our data showed that premixed insulin being most commonly used insulin. All patients used Insulin Pen as delivery device and larger proportions of them were self injecting insulin. All patients felt mild hypoglycemia which can be improved by increased utilization of glucometer. Jour of Diab and Endo Assoc of Nepal 2017; 1(1): 3-7